1998
DOI: 10.1128/iai.66.5.1934-1940.1998
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Cytolethal Distending Toxin Causes a G 2 -Phase Cell Cycle Block

Abstract: Cytolethal distending toxin (CDT) from the diarrheagenic bacteriumCampylobacter jejuni was shown to cause a rapid and specific cell cycle arrest in HeLa and Caco-2 cells. Within 24 h of treatment, CDT caused HeLa cells to arrest with a 4N DNA content, indicative of cells in G2 or early M phase. Immunofluorescence studies indicated that the arrested cells had not entered M phase, since no evidence of tubulin reorganization or chromatin condensation was visible. CDT treatment was also shown to cause HeLa cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
108
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(115 citation statements)
references
References 35 publications
4
108
2
1
Order By: Relevance
“…It is currently unknown which bacterial factors are involved in promoting IL-8 secretion; however, IL-8 and other proinflammatory mediators are thought to be important in initiating the host mucosal inflammatory response, which is critical for both the induction of diarrhoea and the clearance of infection. IL-8 production has been attributed to two general mechanisms, one of which is mediated by attachment/invasion (Hickey et al ., 1999) and the other by cytolethal distending toxin (CDT) (Hickey et al ., 2000), a Campylobacter toxin that causes G2 cell cycle arrest in host cells by inflicting DNA damage (Whitehouse et al ., 1998;Lara-Tejero and Galan, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently unknown which bacterial factors are involved in promoting IL-8 secretion; however, IL-8 and other proinflammatory mediators are thought to be important in initiating the host mucosal inflammatory response, which is critical for both the induction of diarrhoea and the clearance of infection. IL-8 production has been attributed to two general mechanisms, one of which is mediated by attachment/invasion (Hickey et al ., 1999) and the other by cytolethal distending toxin (CDT) (Hickey et al ., 2000), a Campylobacter toxin that causes G2 cell cycle arrest in host cells by inflicting DNA damage (Whitehouse et al ., 1998;Lara-Tejero and Galan, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As with the other Proteobacteria pathogens Haemophilus ducreyi, Aggregatibacter actinomycetemcomitans and Shigella dysenteriae, C. jejuni possesses CDT that interferes with normal cell cycle progression, resulting in G 2 arrest (Pickett et al, 1996;Purdy et al, 2000;Whitehouse et al, 1998). CDT (encoded by the cdtABC operon) is the only identified toxin in C. jejuni, yet the role that host metabolites such as bile salts play in inducing CDT secretion is unclear.…”
mentioning
confidence: 99%
“…Cytolethal distending toxin treatment of a wide range of eukaryotic cells have been shown to result in a cell cycle arrest in either the G 1 or G 2 ⁄ M phase [38][39][40][41][42] which is most likely mediated by CDT-induced DNA double-strand breaks (DSB) [43][44][45][46][47]. In a number of studies, T and B lymphocytes showed induction of apoptosis followed by CDT treatment [48][49][50][51].…”
mentioning
confidence: 99%